GEOLOGIC FACTORS CONTROLLING MINERAL CONTENT IN SELECTED TERTIARY COALS - SOUTHERN KALIMANTAN - Binarko Santoso (Puslitbang tekMIRA, 2009)
Geologic aspects, particularly geologic history and depositional environment, have a main role in the distri- bution of mineral matter in association with maceral composition in coal. The Asem-Asem coals include Miocene and Eocene coals, which are associated with clay minerals, quartz, pyrite and carbonate. The average mean mineral content of the Miocene coals (3.9%) is lower than that of the Eocene coals (6.7%). This indicates that the lower content reflects the balance of the subsidence rate and the peat accumulation rate during the Miocene was absolutely different from those during the Eocene. Consequently, this influ- enced the mineral input to the respective peats. The lower mineral content of the Miocene coals is associated with the bright lithotypes or the vitrinite-rich coals. Otherwise, the higher one of the Eocene coals is associ- ated with dull lithotypes or the vitrinite-poor coals. Methods applied in this study include optical microscopy (reflected-white light and fluorescence mode), X- ray diffraction and scanning electron microscopy (SEM). Clay minerals dominated by kaolinite were deposited in a fresh water environment during peat formation. Most of the minerals are syngenetic in origin. However, some of them are considered to be epigenetic (these clays are in fissures). Quartz is mostly syngenetic, although epigenetic quartz is present. Pyrite takes place as grains and a replacement mineral in organic matter. Calcite is mostly epigenetic occurring in fractures and fissures.